The relationship of the rule of parents with sexual initiation on adolescent in class XI - Derang, Imelda; Ginting , Amnita; Manihuruk, Erika Dwi Putri (Institute of Accounting Research and Novation (IARN), 2023)
Sexual initiation is the initial stage for a person to recognize the desire to carry out deeper sexual acts, therefore the role of parents is very important in the life and development of children. Parents have a role in educating, providing role models, guiding children and supervising their children in preventing sexual initiation behavior. The purpose of this study was to determine the relationship between parental roles and sexual initiation on adolescents in class XI SMA Negeri 5 Medan City. The research design used in this study uses a cross sectional. Sampling using purposive sampling technique a sample size of 81 respondents. The instrument uses is a questionnaire with data analysis using the Chi-square. The results showed that the role of good parents are 70 people (86.4%), light sexual initiation are 69 people (85.2%).test statistic chi-square with a p-value of 0.000 (p<0.05) showed that there is a relationship between the role of parents and sexual initiation in class XI of SMA Negeri 5 Medan. It is expected that parents will set a time limit in using gadgets/social media and spend time with their children to discuss